Comparative effectiveness of nafcillin or cefazolin versus vancomycin in methicillin-susceptible Staphylococcus aureus bacteremia - Schweizer, Marin L (BioMed Central, 2011)
BACKGROUND: The high prevalence of methicillin-resistant S. aureus (MRSA) has led clinicians to select antibiotics that have coverage against MRSA, usually vancomycin, for empiric therapy for suspected staphylococcal infections. Clinicians often continue vancomycin started empirically even when methicillin-susceptible S. aureus (MSSA) strains are identified by culture. However, vancomycin has been associated with poor outcomes such as nephrotoxicity, persistent bacteremia and treatment failure. The objective of this study was to compare the effectiveness of vancomycin versus the beta-lactam antibiotics nafcillin and cefazolin among patients with MSSA bacteremia. The outcome of interest for this study was 30-day in-hospital mortality. METHODS: This retrospective cohort study included all adult in-patients admitted to a tertiary-care facility between January 1, 2003 and June 30, 2007 who had a positive blood culture for MSSA and received nafcillin, cefazolin or vancomycin. Cox proportional hazard models were used to assess independent mortality hazards comparing nafcillin or cefazolin versus vancomycin. Similar methods were used to estimate the survival benefits of switching from vancomycin to nafcillin or cefazolin versus leaving patients on vancomycin. Each model included statistical adjustment using propensity scores which contained variables associated with an increased propensity to receive vancomycin. RESULTS: 267 patients were included; 14% (38/267) received nafcillin or cefazolin, 51% (135/267) received both vancomycin and either nafcillin or cefazolin, and 35% (94/267) received vancomycin. Thirty (11%) died within 30 days. Those receiving nafcillin or cefazolin had 79% lower mortality hazards compared with those who received vancomycin alone (adjusted hazard ratio (HR): 0.21; 95% confidence interval (CI): 0.09, 0.47). Among the 122 patients who initially received vancomycin empirically, those who were switched to nafcillin or cefazolin (66/122) had 69% lower mortality hazards (adjusted HR: 0.31; 95% CI: 0.10, 0.95) compared to those who remained on vancomycin. CONCLUSIONS: Receipt of nafcillin or cefazolin was protective against mortality compared to vancomycin even when therapy was altered after culture results identified MSSA. Convenience of vancomycin dosing may not outweigh the potential benefits of nafcillin or cefazolin in the treatment of MSSA bacteremia.